Pembandingan Kinerja Keuangan Perusahaan Asuransi Syariah dan Non-Syariah Terbuka di Indonesia - Alwan Sri Kustono (Universitas Jember, 2017)
This research was conducted to compare the different of financial performance between sharia and non sharia conventional insurance company listed in Indonesian Stock Exchange. Population in this research are insurance companies that listed in Indonesian Stock Exchange. Data is collected from of the insurance company during three years since 2012-2014. Five variables are used to measure financial performance of insurance company. The variables are profitability, debt ratio, capital structure, earning per share, and equity per share. The results of this research show that earning per share and equity per share of sharia insurance company were better than non-sharia companies, but profitability, debt ratio, and capital structure were worse than non-sharia companies. Keywords: rentability, debt ratio, capital structure, earning per share, equity per share